Can Laue microdiffraction be used to solve and refine complex inorganic structures?. (10th November 2013) - Dejoie, Catherine; McCusker, Lynne B.; Baerlocher, Christian; Kunz, Martin; Tamura, Nobumichi
<x xml:space="preserve">Abstract</x> The white‐beam Laue diffraction experiment is an attractive alternative to the more conventional monochromatic one for single‐crystal structure analysis, because it takes full advantage of the X‐ray energy spectrum of a synchrotron source and requires no rotation of the crystal in the beam. Therefore, it could be used for structural characterizations under in situ or operando conditions. The potential of Laue diffraction was recognized and exploited by the protein community many years ago, and the methodology, which involved positioning and rotating the crystal in the beam, has been successfully applied to the determination of both protein and small‐molecule crystal structures. Here, it is proposed that the specificities of Laue diffraction are exploited to study randomly oriented stationary microcrystals of inorganic materials. In order to determine the best strategy for collecting a reasonable quantity of data from stationary crystals, a series of simulations on four model structures for three experimental setups have been performed. It is shown that the structures of the four samples can be solved with the dual‐space method in SHELX, even though the data sets are highly incomplete and much of the low‐resolution part is missing. The experimental setup and data collection strategy for measuring such microcrystals have been developed on BL12.3.2 at the Advanced Light Source in Berkeley. The intensities of reflections with one and two harmonics can be extracted reliably by exploiting the tunable low‐energy threshold of a Pilatus detector. In this way, the number of usable reflections can be increased from 75 to 95%. Such Laue microdiffraction data have been measured and used successfully to refine the structures of the model samples.